The Effectiveness of Listen-Read-Discuss and Contextual Redefinition Strategies in Teaching Reading Comprehension to EFL Learners with Different Levels of Motivation - Aulia Rohman, Isa; Suwandi, Suwandi (Universitas Negeri Semarang, 2021)
This study aims to analyze how effective the listen-read-discuss (LRD) strategy and contextual redefinition (CR) strategy in teaching reading comprehension to EFL learners with different motivation levels. This paper explained the result of experimental research on reading comprehension skills to students with high and low motivations at SMP Islam Nudia Semarang. This study used a 2x2 factorial design in the experimental study. It was used to collect the data from 40 students divided into two groups; they were experimental group 1 and experimental group 2. They were treated with different strategies: LRD and CR strategies. Test and questionnaire were used to collect the data in this study. The data was analyzed using ANOVA to prove the hypotheses. The result showed a significant difference between LRD and CR strategies to teach reading comprehension to students with high and low motivations. The Contextual Redefinition (CR) strategy effectively teaches reading comprehension to high and low motivation levels than the Listen-Read-Discuss (LRD) strategy. Based on ANOVA analysis, there were no interaction among the LRD and CR strategies, students' motivation, and teaching reading comprehension.